Pengaruh Konsentrasi Koagulan Terhadap Proses Pengolahan Air Di PDAM Surya Sembada Kota Surabaya - Rafif Permata Dwidewitra; M. Miftahul Huda; Tuhu Agung Rachmanto (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Coagulation is one of the processes of water treatment by the addition of chemicals, the purpose of which is to bind particles like particles or dissolve so that they clump. Coagulation concentration definitely affects the coagulation process carried out. In addition, the addition of coagulation also affects the water produced for distribution. Testing of the impact of coagulant concentrations on raw water treatment processes has been carried out on the PDAM Surya Sembada Surabaya. The use of laboratory testing methods is done to see the water quality when using different coagulants. The results of the analysis obtained that the difference in the concentration of coagulants has an influence on the process of water treatment, this is due to several factors that support the existence of variation in the use of the coagulation concentration.